Manipulation of fullerene superstructures by complexing with polycyclic aromatic compounds. Issue 43 (27th October 2017) - Tang, Qin; Zhang, Shufang; Liu, Xinbang; Sumita, Masato; Ishihara, Shinsuke; Fuchs, Harald; Ji, Qingmin; Shrestha, Lok Kumar; Ariga, Katsuhiko
Abstract : Fullerene superstructures with various nanofeatures were fabricated by the intercalation of polycyclic aromatic compounds (naphthalene, anthracene and pyrene) during the growth of fullerene crystals. Abstract : Polycyclic aromatic compounds (naphthalene, anthracene and pyrene) have been intercalated into the superstructures of fullerene nanowhiskers, using a facile liquid–liquid interfacial precipitation (LLIP) method. Due to the interaction between polycyclic molecules and fullerene, the growth of fullerene crystals was interfered in comparison to the fullerene crystal growth without the polycyclic molecules, resulting in the formation of fullerene superstructures with various nanofeatures. Moreover, the fluorescence emissions of the fullerene superstructures were significantly changed due to the intercalation of the polycyclic molecules, implying the influence of molecular packing on the electron transfer within the nanostructures. These results may bring new insights on the control of fullerene nanostructures and to manipulate their optical properties in optoelectronic devices.